2022
DOI: 10.1002/aoc.6939
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of benzyl alcohols by silica‐supported heterogeneous catalyst containing dioxidotungsten(VI) core

Abstract: A dioxidotungsten(VI) complex, [WO 2 L(CH 3 OH)]Á0.5(CH 3 OH) (1), was prepared by the reaction of WCl 6 and tridentate ONO-donor Schiff base ligand (H 2 L) that was obtained from the reaction of 2-hydroxy-1-naphthaldehyde with 4-aminobenzoic hydrazide. Both H 2 L and 1 were characterized by various analyses including nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FT-IR) and UV-Vis spectroscopy, and elemental analysis. Single crystal X-ray analysis was used to determine the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…[18] Preparing appropriate coordination compounds containing suitable functional groups to prepare heterogeneous catalysts is one of the challenges in this field. [19] Structural characterization of coordination compounds in the heterogeneous systems is the next challenge in this area. [20] Professional designing of ligands with appropriate functional groups and determining the structure of coordination compounds by single crystal X-ray diffraction studies before heterogenization process are two acceptable methods to overcome to these challenges and provide heterogeneous catalysts with greater structural accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Preparing appropriate coordination compounds containing suitable functional groups to prepare heterogeneous catalysts is one of the challenges in this field. [19] Structural characterization of coordination compounds in the heterogeneous systems is the next challenge in this area. [20] Professional designing of ligands with appropriate functional groups and determining the structure of coordination compounds by single crystal X-ray diffraction studies before heterogenization process are two acceptable methods to overcome to these challenges and provide heterogeneous catalysts with greater structural accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Singlets at 8.75-8.63 ppm and 3.77-3.73 ppm were assigned to the CH=N and OCH 3 groups, respectively. The aromatic moieties gave signals in the range of 9.19-6.65 ppm [45]. In the 13 Due to the donor properties of the solvent DMSO-d 6 , the metallosupramolecular nature of complexes 1-4 and the presence of ancillary ligand in the mononuclear complexes 1a-4a were disrupted, and complexes [(MoO 2 ) 2 (L 1-4 )(DMSO)] appeared instead.…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…29 This enzyme, with the ability to cure germ cell cancers, Wilm's tumour, Ewing's sarcoma, Kaposi's sarcoma, gestational choriocarcinoma, and rhabdomyosarcoma, 30 catalyses the coupling of substituted o -aminophenol to phenoxazinone chromophore in the synthesis of actinomycin D. 31 Our present study describes the synthesis of homogeneous dioxidotungsten( vi ) complex of deferasirox {4-[3,5-bis(2-hydroxyphenyl)-1 H -1,2,4-triazol-1-yl]benzoic acid, H 3 hptb, I }, its heterogeneous analogue immobilized on amine-functionalized titania and their application in functional mimicking the phenoxazinone synthase (PHS) enzyme. Though SiO 2 , Fe 3 O 4 and other inorganic materials are available for the immobilization of metal complexes, 32–35 we recently observed that TiO 2 has worked as an excellent support in immobilizing molybdenum complexes. 26,36 Further, such TiO 2 -supported metal complexes based catalysts are recyclable and re-usable.…”
Section: Introductionmentioning
confidence: 99%